2020
DOI: 10.30607/kvj.670744
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Amyloid-A, Haptoglobin, Ceruloplasmin and Albumin Levels in Dogs Which are Infected with Babesia canis

Abstract: In this study, we aimed to determine the serum haptoglobin (Hp), serum amyloid-A (SAA), ceruloplasmin (Cp) and albümin (Alb) levels in the dogs which are naturally infected with Babesia canis. 20 patient dogs which were diagnosed as B. canis by staining of their blood smears with giemsa method, which were brought to Kafkas University Veterinary Faculty Internal Medicine Department clinics formed the material of the study. 10 Healthy dogs were used for control. The serum Hp, SAA, Cp and Alb levels of the sick a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition to its acute-phase protein properties, Cp is involved in the transport of antioxidants and copper in the bloodstream (Ulutaş et al 2008;Gökce and Bozukluhan 2009;Tuna and Ulutaş 2015). This characteristic makes it a potential diagnostic marker for diseases (Erkılıç et al 2019;Kırmızıgül et al 2020). In a study conducted by Nisbet et al (2008) in cattle with cystic echinococcosis, they found that serum Cp levels were higher in the patient group compared to the group of healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its acute-phase protein properties, Cp is involved in the transport of antioxidants and copper in the bloodstream (Ulutaş et al 2008;Gökce and Bozukluhan 2009;Tuna and Ulutaş 2015). This characteristic makes it a potential diagnostic marker for diseases (Erkılıç et al 2019;Kırmızıgül et al 2020). In a study conducted by Nisbet et al (2008) in cattle with cystic echinococcosis, they found that serum Cp levels were higher in the patient group compared to the group of healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…Cp plays a crucial role in catalyzing the oxidation of toxic iron. By catalyzing the conversion of ferrous iron (Fe2+) to ferric iron (Fe3+), ceruloplasmin helps to safeguard tissues from damage caused by free radicals (Sevgisunar et al, 2014;Karabulut and Gülay, 2016;Kırmızıgül and Arslan, 2020). Ceruloplasmin also exhibits its protective activity by safeguarding polyunsaturated fatty acids present in erythrocyte membranes from the harmful effects of reactive oxygen species (Karabulut and Gülay, 2016).…”
mentioning
confidence: 99%